RATIONAL ANTIVIRAL TREATMENT OF ACUTE RESPIRATORY INFECTIONS IN OUTPATIENT CLINIC - M.G. Lukashevich (Вопросы современной педиатрии)
An epidemiology and clinical symptomatology of frequently occurred acute respiratory viral infections (ARVI) and opportunities of treatment of patients with these diseases in outpatient clinics are described. New information about effectiveness and safety of antiviral medications in treatment and prophylaxis of ARVI in children are discussed.Key words: children, acute respiratory viral infections, antiviral medications, interferon, interferon inductors.